2016
DOI: 10.1177/0885328216681893
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fluorescein-grafted polyurethane for potential application in biomedical tracing

Abstract: Redesigned multifunctional biopolymers represent a novel building bridge for interdisciplinary collaborations in biomaterials development. We prepared fluorescein-grafted polyurethane scaffolds (PU-C1, PU-C5, and PU-B1) to meet both clinical needs and biological safety evaluations, using different contents of calcein and different synthesis procedures for potential biomedical tracing. X-ray diffraction, infrared, X-ray photoelectron spectroscopy, nuclear magnetic resonance, scanning electron microscopy, and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It is well known that there is a class of polymer materials that can be synthesized as “soft or hard scaffolds” by different segmented structures [16]. The synthetic polymer called polyurethane (PU) has been applied in tissue engineering with the advent of a wide range of mechanical and physical properties by changing the ratio of soft and hard segments and the composition [17,18]. PU exhibit diverse properties with a self-foaming porous and unique segmented structure, excellent and varying mechanical properties, and good biocompatibility, which could be considerable interest to specific tissue [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that there is a class of polymer materials that can be synthesized as “soft or hard scaffolds” by different segmented structures [16]. The synthetic polymer called polyurethane (PU) has been applied in tissue engineering with the advent of a wide range of mechanical and physical properties by changing the ratio of soft and hard segments and the composition [17,18]. PU exhibit diverse properties with a self-foaming porous and unique segmented structure, excellent and varying mechanical properties, and good biocompatibility, which could be considerable interest to specific tissue [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, a PU-based composite scaffold with castor oil and nano-hydroxyapatite prepared for bone regeneration, but the increased cross-linking density of the PU network inhibited the degradation even if the implantation was operated into rabbits for 24 weeks . Recently, a series of undegradable PU has been investigated in which different synthesis procedures have affected the fluorescence efficiency apparently . Also, CPU-5 prepared by chemical grafting with calcein (the molar ratio of calcein/soft-segment of 0.5%) as chain extender has excellent fluorescence stability and biocompatibility .…”
Section: Resultsmentioning
confidence: 99%
“…23 Pristine calcein and CPU-5 have similar fluorescence intensities, both around 2000. 23 It was surprising that the intensity of the emission of PU-5 was dramatically higher than the same concentration of pristine calcein solution (3×) and CPU-5 (3×), and the emission maximum of PU-5 presented a hypsochromic shift (Figure 1C). Hu et al found that chemical grafting of fluorescent molecules (aminofluorescein) into the PU backbone would result in a hypsochromic shift of the emission wavelength of the fluorescent PU due to an increase in the polarity of the fluorescent molecule.…”
Section: Preparation Degradable Fluorescence-grafted Copolymers (Pu-5)mentioning
confidence: 95%
See 1 more Smart Citation
“…150,[177][178][179] PU nanofibers prepared by electrostatic spinning mimic the reticular structure of the ECM; the addition of conductive NMs (eg MWCNTs, GO, and Au-NPs) increases the jet charge density of the preparation, reducing the PU nanofiber diameter and increasing the porosity, and provides an electrophysiological environment for directional cell attachment, migration, and proliferation. 78,[180][181][182][183]…”
Section: Pu Nanocomposite Forms and Preparationmentioning
confidence: 99%